2021
DOI: 10.1093/mnras/staa3383
|View full text |Cite
|
Sign up to set email alerts
|

Optical and spectral observations and hydrodynamic modelling of type IIb supernova 2017gpn

Abstract: In this work we present the photometric and spectroscopic observations of type IIb supernova 2017gpn. This supernova was discovered in the error-box of the LIGO/Virgo G299232 gravitational-wave event. We obtained the light curves in the B and R passbands and modelled them numerically using the one-dimensional radiation hydrocode stella. The best-fitting model has the following parameters: the pre-SN star mass and the radius are M ≈ 3.5 M⊙ and R ≈ 50 R⊙, respectively; the explosion energy is $E_{\rm exp} \appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The 56 Ni masses of SE SNe have also been computed through hydrodynamical modeling of light curves (e.g., Utrobin 1996;Nakamura et al 2001;Mazzali et al 2002;Sauer et al 2006;Tanaka et al 2009;Tsvetkov et al 2009;Bersten et al 2012Bersten et al , 2014Bufano et al 2014;Folatelli et al 2014;Ergon et al 2015;Folatelli et al 2015;Morales-Garoffolo et al 2015;Fremling et al 2016;Taddia et al 2016Taddia et al , 2018bBersten et al 2018;Balakina et al 2021). In particular, Taddia et al (2018b) found that the 56 Ni masses inferred with the Arnett model are consistent with those computed with the hydrodynamical models generated with the code of Bersten et al (2011).…”
Section: Introductionmentioning
confidence: 81%
“…The 56 Ni masses of SE SNe have also been computed through hydrodynamical modeling of light curves (e.g., Utrobin 1996;Nakamura et al 2001;Mazzali et al 2002;Sauer et al 2006;Tanaka et al 2009;Tsvetkov et al 2009;Bersten et al 2012Bersten et al , 2014Bufano et al 2014;Folatelli et al 2014;Ergon et al 2015;Folatelli et al 2015;Morales-Garoffolo et al 2015;Fremling et al 2016;Taddia et al 2016Taddia et al , 2018bBersten et al 2018;Balakina et al 2021). In particular, Taddia et al (2018b) found that the 56 Ni masses inferred with the Arnett model are consistent with those computed with the hydrodynamical models generated with the code of Bersten et al (2011).…”
Section: Introductionmentioning
confidence: 81%
“…In Dessart et al (2018b), the radiation hydrodynamics (RHD) code v1d and the non-LTE radiative transport code CMFGEN were used for modeling the evolution of the ejecta and obtaining the optical light curves, respectively. Several studies adopted the STELLA code (Blinnikov et al 1998(Blinnikov et al , 2006Blinnikov & Tolstov 2011), a 1D RHD code that implicitly calculates the radiative transfer over multiple frequency bands, in order to generate spectral energy distributions (SEDs) and obtain optical light-curve models (see Tsvetkov et al 2009Tsvetkov et al , 2012Nakaoka et al 2019;Balakina et al 2021). Some studies assume that the SEDs from an SN are blackbody spectra of the effective temperature at the photosphere (usually defined by the Rosseland mean opacity) or a color temperature obtained from an analytical approximation (Bersten et al 2012;Piro et al 2017;Bersten et al 2018;Eldridge et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic energy of SN 2019tua can be calculated, ∼0.5 × 10 51 erg. SN 2019tua has a lower kinetic energy compared to those of some Type IIb SNe, such as SN 2017gpn (∼3 × 10 51 erg;Balakina et al 2021), SN 2020acat (∼1.2 × 10 51 erg; Medler et al 2022), SN 2011fu (∼1.3 × 10 51 erg; Morales-Garoffolo et al 2015), ASASSN-14dq (∼1.24 × 10 51 erg; Singh et al 2018), SN 2020cxd…”
mentioning
confidence: 98%